Estudo da composição química da jaca (Artocarpus heterophyllus Lam.) desidratada, in natura e liofilizada - Basso, Adriano Martinez (2017)
This work had as objectives to determine the physicochemical and mineral compositions of the dehydrated seeds of the soft jackfruit (SJ) and of the hard jackfruit (HJ), of the dehydrated, in nature and lyophilized pulps of the SJ and HJ. For this, were determined the percentages of: moisture, ash, lipids, protein and carbohydrate. The concentrations of the elements calcium, copper, iron, magnesium, chromium, manganese, potassium, sodium, zinc, nickel and cobalt were analyzed by ICP-OES. The results showed that the seeds of SJ and of HJ have very close bromatological compositions: 63% moisture, 18% carbohydrate, 15% protein and 3% ash. The major difference was in the lipids contente (0,4% - SJ and 0,9% - HJ). The mineral compositions are quite distinct. Potassium and magnesium are the most abundant in both varieties (96% - SJ and 93% - HJ). The seeds of HJ have 5,5 times more Na, 24% more Ca, 3 times more Zn and 2% more K. The seeds of SJ have 32% more Fe, 37% more Mn and 16% more Mg. From a physicochemical point of view, the pulps have a great distinction. The pulp of HJ has 9,5 times more lipids and twice the carbohydrate. The pulp of SJ has 10% more moisture and 14% more ash. The protein content is very similar. In pulps, the composition of minerals is quite different, although potassium and magnesium are the major elements in the two varieties (96% - SJ and 93% - HJ). The pulp of SJ has 33% more K, 29% more Mg, 26% more Mn, 48% more Na, 16% more Cu, 24% more Fe and 5% more Zn. The pulp of HJ has 45% more Ca, which may explain its greater firmness. The chemical composition of the pulps in nature of SJ and HJ are very similar in relation to the concentrations of Fe, Cu, Mn and Mg. The HJ in nature pulp has 2,6 times more Ca and 27% more Zn. The in nature soft variety has 5% more K and 25% more Na. The freeze-drying preserved the carbohydrate content in the pulps of the two varieties of jackfruit. The SJ lyophilized pulp had the lower metal content than the pulp dehydrated in the oven. The results were submitted to the paired t test, with 95% significance, to infer the significance of the equality or inequality of the parameters compared.